Symmetry in the context of the Almost Contact 3-Structure and Almost Quaternion Structure - Kumar, Nanda Kishor (Pragnya Sarathi प्रज्ञा-सारथि, 2025)
The aim of this paper is to explores the characteristics, relationships, and applications of nearly contact 3-structure and nearly quaternion structure in current mathematical study, as well as their foundations. The Interplay between almost contact 3-structure and almost quaternion structure and significance and future direction have also been described. The study of symmetry in Almost Contact 3-Structures and Almost Quaternion Structures provides deep insights into differential geometry and mathematical physics. These structures serve as a bridge between classical Riemannian geometry and modern physical theories, with ongoing research continuing to explore their rich algebraic and geometric properties.